Social Entrepreneurship Projects in the English Class: A Pandemic Multimodal Experience - Jhooni Quintero-González; Amparo Clavijo-Olarte (Asociación Colombiana de Profesores de Ingles, 2022)
This exploratory qualitative study shares an innovative experience with twenty-three EFL undergraduate students in the Business Administration Program at a private university in Colombia. It aimed at positioning them as problem solvers and connecting their background as sources for EFL learning. We explored how business administration students problematized their communities to propose social solutions during the pandemic. Data were collected from students' reflective journals, students' artifacts, and a survey. In groups, the students explored cultural practices for shopping, economy, and pet-related issues to propose a social entrepreneurship project. Eleven business projects emerged as a result of students' socially-oriented concerns, critical skills, and multimodal experiences.